Click to Chat

1800-1023-196

+91-120-4616500

CART 0

• 0

MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping
`        In triangle ABC if cosA/b =cosB/a then prove that the triangle is either a right angled or an isosceles triangle.`
2 years ago

```							Using the Law of cosines for any triangle (here is very important, we are not assuming the type of that triangle, Law of cosines applies to any triangle), so in the triangle ABC we have: cosA = (b2 + c2 - a2)/2bc So the left side of that equation will be:   cosA/b  = (b2+ c2 - a2)/ (2*b2*c)      (one more b in the denominator ) As the same reason, the right side of that equation will be:  cosB/a =  (a2 +c2 - b2)/ (2*a2*c) So if  cosA/b = cosB/a  We will have that  (b2+ c2 - a2)/ (2*b2*c)  =  (a2 +c2 - b2)/ (2*a2*c)  Then we simplify that equation as following steps: (b2+ c2 - a2)/ b2 = (a2 +c2 - b2)/ a2         (both sides have the 2c in the denominator, so 2c eliminated) then in either of the two sides, we divide the denominator into the bracket, then we get: 1+ c2/b2 - a2/b2  =  1 + c2/a2 - b2/a2 Then we eliminate the same part of both sides, which is   1  ,we will get an equation as: c2/b2 - a2/b2= c2/a2 - b2/a2 We multiply a2b2 at each side (because neither a nor b is zero for they are sides of triangle), then we get c2a2 - a4 = c2b2 - b4 move the c2 to same sides, we will get: c2(a2-b2) = a4 - b4 = (a2 + b2) (a2 - b2) Ok, till now we get an equation as : c2 (a2-b2) = (a2+b2) (a2-b2)      -------------------------- EQUATION_ONE Now we have to discuss the different situation: 1. If a2-b2 = 0, which means a = b (because a and b are sides of triangle, so they are positive), then that EQUATION_ONE will be satisfied no matter c is what.  So that means the triangle will be isosceles triangle, as a=b. 2. If (a2-b2) is not 0, then we can eliminate the (a2-b2) in both sides of the EQUATION_ONE . Then we will have: c2=a2+b2 which means the triangle is a right angle triangle    In conclusion, if cosA/b = cosB/a, we can get c2 (a2-b2) = (a2+b2) (a2-b2) by using Law of cosines, and then we can get that either  c2=a2+b2  or a2-b2=0   can satisfy that equation above, which means the triangle is either right angle triangle or an isosceles triangle.
```
2 years ago
Think You Can Provide A Better Answer ?

## Other Related Questions on Trigonometry

View all Questions »  ### Course Features

• 731 Video Lectures
• Revision Notes
• Previous Year Papers
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Test paper with Video Solution  ### Course Features

• 31 Video Lectures
• Revision Notes
• Test paper with Video Solution
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Previous Year Exam Questions